Tokoh Kabayan Sebagai Inspirasi Torotot Heong the Song of Kabayan - DEDEN HAERUDIN (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2008)
Kabayan as an Inspiration of Torotot Heong The Song Of Kabayan. The theater art creation of Torotot Heongthe Song of Kabayan is a process that is inspired by the characters of folklore in Sundanese literature, Kabayan. InSundanese society, Kabayan is a stunt character from parable, a symbolic story, in the community as a media tonotify precept or wisdom. Kabayan is regarded as character with characteristic of Sundanese culture that hold on to“Cageur jeung Bageur” living guide (hale and healthy, and kind hearted). The creation process of Torotot Heongthe Song of Kabayan is performing into several stages and working methods according to Patri Pavis. It is startedby selecting the Kabayan’s Story to under take into the script. The next stage is doing some preparation for StagingProcess. The creating process is conducted through the mise en scene show’s appearance, perform into idea identification stage, artistic observation of cultural resources, the artist perspective and performance realization. TorototHeong the Song of Kabayan performances are the ultimate stage for the creative process of the hardworking teamwith a lot of effort to accomplish a communicative performance and appreciate well by the audience.